Adult Rapıd Maxıllary Expansıon - Ayhan Enacar; Mehmet Özgen; Murat Demirhanoğlu (Galenos Yayinevi, 1993)
In patients with maxillary horizontal deficiency, maxillary collapse, nasal stenosis, arch length problem, temporomandibuler disorders and arch coordination prior to orthognathics the use of rapid maxillary expansion (RME) has become an accepted initial step in comprehensive orthodontic treatment. On the other hand, in adults where maxillary horizontal deficiency is present, the application of RME is controversial Generally, it has been widely believed that females 16 or older and males 19 or older with maxillary constriction require a surgical maxillary expansion or must be compromised with buccal flaring. However, there are views stating that if a % 5 closure is set as a limit for splitting the intermaxillary suture, this will not be reached in most patients younger than 25 years of age. Based on this opinion, in our clinic we attempt to split the midpalatal suture with non surgical means in adult patients. In this paper, four instances of adult rapid maxillary expansion is presented and significance of conservative RME approach in adult orthodontics is emphasized.